2002
DOI: 10.1093/toxsci/68.1.226
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Carcinogenicity with the Thiazolidinedione Antidiabetic Agent Troglitazone

Abstract: Carcinogenic potential of the thiazolidinedione antidiabetic troglitazone was assessed in 104-week studies in mice and rats. Mice were given 50, 400, or 800 mg/kg, male rats 100, 400, or 800 mg/kg, and female rats 25, 50, or 200 mg/kg. Vehicle and placebo controls were included. Survival was significantly decreased in both sexes of both species at high doses, but was adequate for valid evaluation of carcinogenicity. Hypertrophy and hyperplasia of brown adipose tissue was observed in both species at all doses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…Increased incidence of liver hemangiosarcomas and hepatocellular carcinomas occurred with TGZ in mice at 20 and 40 times the human therapeutic dose. 41 No tumors of any type were induced by TGZ in rats at 40 times or in monkeys at 160 times the human therapeutic dose. [41][42][43] Furthermore, TGZ was neither mutagenic in bacteria nor clastogenic in bone marrow of mice or rats, indicating no genotoxic risk.…”
Section: Liver Fibrosis and Cancermentioning
confidence: 97%
See 3 more Smart Citations
“…Increased incidence of liver hemangiosarcomas and hepatocellular carcinomas occurred with TGZ in mice at 20 and 40 times the human therapeutic dose. 41 No tumors of any type were induced by TGZ in rats at 40 times or in monkeys at 160 times the human therapeutic dose. [41][42][43] Furthermore, TGZ was neither mutagenic in bacteria nor clastogenic in bone marrow of mice or rats, indicating no genotoxic risk.…”
Section: Liver Fibrosis and Cancermentioning
confidence: 97%
“…41 No tumors of any type were induced by TGZ in rats at 40 times or in monkeys at 160 times the human therapeutic dose. [41][42][43] Furthermore, TGZ was neither mutagenic in bacteria nor clastogenic in bone marrow of mice or rats, indicating no genotoxic risk. 152 In addition, none of the analyzed 165 tumors in mice had inactivating p53 mutations, and fewer than 5% had mutations of Ki-and Ha-ras oncogenes.…”
Section: Liver Fibrosis and Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…Common tumor findings in rodent carcinogenicity studies of PPAR agonists are hemangioma/hemangiosarcoma, urinary bladder/renal pelvic tumors, and lipoma/liposarcoma. 1) Hemangioma/hemangiosarcoma: These tumors were observed in multiple organs such as the spleen, liver, skin and adipose tissues of male and female CD-1 and B6C3F1 mice and hamsters treated with 8/12 PPAR agonists (4 γ agonists including troglitazone 11,12 and 4 dual agonists). It has also been reported that hemangiomatous hyperplasia and angiectasia were observed in rodent and non-rodent species treated with the other compounds of the same class.…”
Section: Results Of Carcinogenicity Studies Of Ppar γ and α/γ Dual Agmentioning
confidence: 99%